2008
DOI: 10.1208/s12249-008-9105-1
|View full text |Cite
|
Sign up to set email alerts
|

Niosome-Encapsulated Gentamicin for Ophthalmic Controlled Delivery

Abstract: Abstract. The objective of the present research was to investigate the feasibility of using non-ionic surfactant vesicles (niosomes) as carriers for the ophthalmic controlled delivery of a water soluble local antibiotic; gentamicin sulphate. Niosomal formulations were prepared using various surfactants (Tween 60, Tween 80 or Brij 35), in the presence of cholesterol and a negative charge inducer dicetyl phosphate (DCP) in different molar ratios and by employing a thin film hydration technique. The ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
164
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(183 citation statements)
references
References 35 publications
18
164
1
Order By: Relevance
“…In this study, a comparison has been made between spans-and Tweens-loading GNA, the results of the DLS study are shown in Table 1. The studies with the sizes gave us a qualitative idea of the niosomal delivery systems prepared using Spans smaller in the size than that of Tweens, the similar results were reported for Gentamicin niosomes (Abdelbary & El-gendy, 2008). This finding may be due to Spans with shorter alkyl chains and lower HLB values than Tweens, therefore causing a reduction of the repulsion forces between the hydroxyl groups of Spans and the carboxyl groups of the anticancer drug, thus it should be able to produce smaller size PEGylated niosomes.…”
Section: Characteristics Of P-gna-nisvssupporting
confidence: 63%
“…In this study, a comparison has been made between spans-and Tweens-loading GNA, the results of the DLS study are shown in Table 1. The studies with the sizes gave us a qualitative idea of the niosomal delivery systems prepared using Spans smaller in the size than that of Tweens, the similar results were reported for Gentamicin niosomes (Abdelbary & El-gendy, 2008). This finding may be due to Spans with shorter alkyl chains and lower HLB values than Tweens, therefore causing a reduction of the repulsion forces between the hydroxyl groups of Spans and the carboxyl groups of the anticancer drug, thus it should be able to produce smaller size PEGylated niosomes.…”
Section: Characteristics Of P-gna-nisvssupporting
confidence: 63%
“…Also, as compared to normal drug solution, niosomes of drug show slow release. 57) Niosomal formulation containing timolol meleate (0.25%) prepared by chitosan coating exhibited more effect on intra ocular tension with fewer side effects as compared to the marketed formulation. …”
Section: In Ophthalamic Drug Deliverymentioning
confidence: 94%
“…Niosomes have been used to deliver drugs like gentamicin to the eye (Abdelbary & El-gendy, 2008). Niosomes are formed from the self-assembling of nonionic amphiphiles in aqueous medium which are able to accommodate hydrophilic and hydrophobic drugs (Carafa et al, 1998;Uchegbu & Vyas, 1998;Abdelbary & El-gendy, 2008).…”
Section: • Metabolism By Enzymesmentioning
confidence: 99%
“…Niosomes are formed from the self-assembling of nonionic amphiphiles in aqueous medium which are able to accommodate hydrophilic and hydrophobic drugs (Carafa et al, 1998;Uchegbu & Vyas, 1998;Abdelbary & El-gendy, 2008). Niosomal ocular drug delivery concept aims to enhance periocular retention, corneal penetration, and provide controlled release in a similae manner to SLNs and liposomes.…”
Section: • Metabolism By Enzymesmentioning
confidence: 99%